A role for Fas II in the stabilization of motor neuron branches during pruning in Drosophila. - Hebbar, S.; Fernandes, J.J. (Developmental Biology, 2005)
During insect metamorphosis, the nervous system is extensively remodeled resulting in the development of new circuits that will execute adult-specific behaviors. The peripheral remodeling seen during development of innervation to the Dorsal Longitudinal (flight) Muscle (DLM) in Drosophila involves an initial retraction of larval neuromuscular junctions followed by adult-specific branch outgrowth. Subsequently, a phase of pruning occurs during which motor neuron branches are pruned back to reveal the stereotypic pattern of multiple contact points (or arbors) along the length of each DLM fiber. In this study, we show that the cell adhesion molecule, Fasciclin II (Fas II), is important for generating the stereotypic pattern. In Fas II hypomorphs, the number of contact points is increased, and the phenotype is rescued by targeted expression of Fas II in either synaptic partner. Arbor development has three distinct phases: outgrowth and elaboration, pruning and stabilization, and expansion of stabilized arbors. Fas II is expressed during the first two phases. A subset of branches is labeled during the elaboration phase, which is likely to initiate a stabilization pathway allowing branches to survive the pruning phase. However, since not all Fas II positive branches are retained, we propose that it primes branches for stabilization. Our data suggest that Fas II functions to restrict branch length and arbor expanse.